PPAR-γ in Melanoma and Immune Cells: Insights into Disease Pathogenesis and Therapeutic Implications - Vladimir Sobolev; Ekaterina Tchepourina; Anna Soboleva; Elena Denisova; Irina Korsunskaya; Alexandre Mezentsev (Cells)
Changes in skin pigmentation, like hyperpigmentation or moles, can affect appearance and social life. Unlike locally containable moles, malignant melanomas are aggressive and can spread rapidly, disproportionately affecting younger individuals with a high potential for metastasis. Research has shown that the peroxisome proliferator-activated receptor gamma (PPAR-γ) and its ligands exhibit protective effects against melanoma. As a transcription factor, PPAR-γ is crucial in functions like fatty acid storage and glucose metabolism. Activation of PPAR-γ promotes lipid uptake and enhances sensitivity to insulin. In many cases, it also inhibits the growth of cancer cell lines, like breast, gastric, lung, and prostate cancer. In melanoma, PPAR-γ regulates cell proliferation, differentiation, apoptosis, and survival. During tumorigenesis, it controls metabolic changes and the immunogenicity of stromal cells. PPAR-γ agonists can target hypoxia-induced angiogenesis in tumor therapy, but their effects on tumors can be suppressive or promotional, depending on the tumor environment. Published data show that PPAR-γ-targeting agents can be effective in specific groups of patients, but further studies are needed to understand lesser-known biological effects of PPAR-γ and address the existing safety concerns. This review provides a summary of the current understanding of PPAR-γ and its involvement in melanoma.